Parasitic phytonematodes - Fotima Sharipovna Nazarova; Khidirnazarov Muhammad (Global Scientific Publishing, 2024)
Nematodes are the most multicellular animals on earth. More than 80,000 species have been described, including around 2,500 plant parasites. Nematodes are elongated, unsegmented, microscopic, eel-like roundworms that may or may not be beneficial. They live in the soil and in the root tissue of plants. Many are good for the soil because they help decompose organic matter. Only a few species of nematodes are parasitic and harmful to crops, as they damage plants by feeding on the roots. Some nematodes attack soil-dwelling insect pests and can be used as biocontrol organisms. Other insect parasitic nematodes can be applied topically to caterpillars, as can a pesticide.
Keywords: Parasite; phytonematode; segment; pesticide